Carbon felt loaded tin single-element composite negative electrode catalytic material and preparation method and application thereof

CN123018005APending Publication Date: 2026-10-30SHAANXI ZHONGYUAN JUNENG ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611377212.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]目前,行业内虽已针对全钒液流电池负极改性及催化材料优化开展了大量研究,但现有技术仍存在诸多不足,传统碳电极活性位点匮乏、金属基催化剂易团聚且稳定性欠佳、部分制备工艺复杂、条件严苛、重现性差,难以实现工业化量产,无法兼顾负极催化效能与电池循环稳定性,进而制约全钒液流电池综合性能提升

Benefits of technology

[0019]本发明所制得的碳毡负载锡单质负极催化材料,可有效提升负极钒离子氧化还原反应的动力学性能,显著缓解电极极化现象、减小反应过电位,进而大幅改善全钒液流电池的性能,有效破解传统负极反应速率缓慢的技术痛点。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018005A_ABST
    Figure CN123018005A_ABST
Patent Text Reader

Abstract

The application belongs to the field of negative electrode catalytic materials, and particularly relates to a carbon felt loaded tin single-element composite negative electrode catalytic material and a preparation method and application thereof, the preparation method comprising the following steps: S1, carbon felt high-temperature pretreatment: the carbon felt is subjected to high-temperature pretreatment under an air atmosphere to obtain pretreated carbon felt; S2, preparation of tin salt precursor solution: the tin salt is dissolved in deionized water, and stirring is performed until the tin salt is completely dissolved to obtain a uniform tin salt precursor solution; S3, impregnation and drying: the pretreated carbon felt obtained in step S1 is immersed in the tin salt precursor solution and impregnated sufficiently, and then taken out and dried, the carbon felt loaded tin single-element negative electrode catalytic material prepared by the application can effectively improve the kinetic performance of the negative electrode vanadium ion redox reaction, significantly relieve the electrode polarization phenomenon and reduce the reaction overpotential, thereby greatly improving the performance of a full vanadium redox flow battery and effectively solving the technical pain point of a slow traditional negative electrode reaction rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of negative electrode catalytic materials technology, and in particular to a carbon felt-supported tin composite negative electrode catalytic material, its preparation method and application. Background Technology

[0002] With the rapid rise of the new energy storage industry and the continuous innovation of long-duration, large-capacity energy storage technologies, the development of anode catalytic materials that combine high catalytic activity and high structural stability has become a core breakthrough for optimizing the overall performance of vanadium redox flow batteries and a key prerequisite for their stable application in large-scale energy storage. Currently, vanadium redox flow battery anodes generally suffer from slow reaction kinetics, prominent electrochemical polarization, and insufficient conductivity and catalytic activity of carbon-based electrodes. During long-term cycling, they are prone to performance degradation and shortened cycle life, failing to meet the actual operational requirements of high-power, long-cycle energy storage systems. Therefore, precise control of the anode interface structure and enhancement of its catalytic activity have become core technologies for overcoming the performance limitations of vanadium redox flow batteries and promoting their engineering applications.

[0003] Currently, although the industry has conducted a lot of research on the modification of the negative electrode and the optimization of catalytic materials for vanadium redox flow batteries, the existing technologies still have many shortcomings. Traditional carbon electrodes lack active sites, metal-based catalysts are prone to agglomeration and have poor stability, some preparation processes are complex, the conditions are harsh, and the reproducibility is poor, making it difficult to achieve industrial mass production. They cannot balance the catalytic efficiency of the negative electrode with the cycle stability of the battery, thus restricting the improvement of the overall performance of vanadium redox flow batteries.

[0004] There is still a lack of efficient, reliable, and practically applicable solutions for the synergistic optimization of anode catalytic activity, structural stability, simplified preparation process, and large-scale application. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing technologies by proposing a carbon felt-supported tin composite negative electrode catalyst, its preparation method, and its application.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A method for preparing a carbon felt-supported tin composite negative electrode catalyst includes the following steps:

[0008] S1. High-temperature pretreatment of carbon felt: The carbon felt is placed in an air atmosphere for high-temperature pretreatment to obtain pretreated carbon felt.

[0009] S2. Preparation of tin salt precursor solution: Dissolve tin salt in deionized water and stir until the tin salt is completely dissolved to obtain a uniform tin salt precursor solution.

[0010] S3. Impregnation and drying: The pretreated carbon felt obtained in step S1 is immersed in tin salt precursor solution for full impregnation, and then dried after removal.

[0011] S4. High-temperature in-situ reduction in argon atmosphere: The dried carbon felt is placed in an inert argon atmosphere for high-temperature heat treatment, which causes an in-situ reduction reaction, so that elemental tin is uniformly deposited and firmly loaded on the surface of the carbon felt and inside the carbon fibers, thus obtaining a preliminary composite material.

[0012] S5. Washing and Drying: The preliminary composite material is washed multiple times with dilute hydrochloric acid to remove various impurities from the system. After drying, the carbon felt-supported tin anode catalyst material is obtained.

[0013] Preferably, in step S1, the high-temperature pretreatment temperature of the carbon felt is 300-500℃; the high-temperature pretreatment time of the carbon felt is 8h-12h.

[0014] Preferably, in step S2, the tin salt is tin chloride pentahydrate; the concentration of tin ions in the tin salt precursor solution is 0.2 mol / L-0.6 mol / L.

[0015] Preferably, in step S4, the high-temperature heat treatment temperature is between 800-1000℃; and the high-temperature heat treatment time is between 10h-15h.

[0016] Preferably, in step S5, the concentration of the dilute hydrochloric acid used for washing is 0.1 mol / L to 0.4 mol / L.

[0017] This invention also proposes an application of a carbon felt-supported tin composite anode catalyst, which is applied to the anode of an all-vanadium redox flow battery.

[0018] The beneficial effects of the carbon felt-supported tin composite negative electrode catalyst, its preparation method, and its application described in this invention are as follows:

[0019] The carbon felt-supported tin anode catalyst material prepared by this invention can effectively improve the kinetic performance of the redox reaction of vanadium ions at the anode, significantly alleviate electrode polarization, reduce reaction overpotential, and thus greatly improve the performance of the all-vanadium redox flow battery, effectively solving the technical pain point of slow reaction rate of traditional anodes.

[0020] Elemental tin can be uniformly dispersed and firmly attached to the surface and internal pores of carbon felt, significantly enhancing the structural integrity of the electrode and its resistance to electrolyte corrosion. This effectively extends the cycle life of vanadium redox flow batteries and meets the long-term, stable operation requirements of large-scale energy storage systems.

[0021] The preparation process is simple and controllable, and it is easy to achieve industrial-scale production, providing a new technical path for the engineering application of high-performance vanadium redox flow battery anodes. Attached Figure Description

[0022] Figure 1 The carbon felt XRD pattern of the carbon felt-supported tin composite negative electrode catalyst material proposed in this invention, its preparation method and application;

[0023] Figure 2 The XRD pattern of the carbon felt-supported tin composite negative electrode catalyst material, its preparation method and application proposed in this invention, is shown in Example 1.

[0024] Figure 3 The XRD pattern of the carbon felt-supported tin composite negative electrode catalyst, its preparation method and application, is shown in Example 2.

[0025] Figure 4 The XRD pattern of the carbon felt-supported tin composite negative electrode catalyst material, its preparation method and application proposed in this invention, is shown in Example 3.

[0026] Figure 5 The XRD pattern of the carbon felt-supported tin composite negative electrode catalyst, its preparation method and application, is shown in Example 4.

[0027] Figure 6 This is a blank carbon felt SEM image showing the morphology of a carbon felt-supported tin composite negative electrode catalyst material proposed in this invention, its preparation method, and its application.

[0028] Figure 7 This is a SEM image of Example 1 of a carbon felt-supported tin composite negative electrode catalytic material, its preparation method, and its application, as proposed in this invention.

[0029] Figure 8 This is a SEM image of Example 2 of a carbon felt-supported tin composite negative electrode catalytic material, its preparation method, and its application proposed in this invention.

[0030] Figure 9 This is a SEM image of Example 3 of a carbon felt-supported tin composite negative electrode catalyst material, its preparation method, and its application proposed in this invention.

[0031] Figure 10 SEM image of Example 4 of the carbon felt-supported tin composite negative electrode catalyst material proposed in this invention, its preparation method and application;

[0032] Figure 11 This is a battery fixture diagram of a carbon felt-supported tin composite negative electrode catalyst material, its preparation method, and its application, as proposed in this invention.

[0033] Figure 12 This is a blank CV diagram of a carbon felt-supported tin composite negative electrode catalytic material proposed in this invention, its preparation method and application;

[0034] Figure 13 The first CV image shows an example of a carbon felt-supported tin composite negative electrode catalytic material, its preparation method, and its application proposed in this invention.

[0035] Figure 14 Figure 2CV shows an example of a carbon felt-supported tin composite negative electrode catalytic material, its preparation method, and its application proposed in this invention.

[0036] Figure 15 Figure 3CV shows an example of a carbon felt-supported tin composite negative electrode catalytic material, its preparation method, and its application proposed in this invention.

[0037] Figure 16 Figure 4CV shows an example of a carbon felt-supported tin composite negative electrode catalytic material, its preparation method, and its application proposed in this invention.

[0038] Figure 17 The blank battery performance diagram shows the carbon felt-supported tin composite negative electrode catalyst material proposed in this invention, its preparation method, and its application.

[0039] Figure 18 Example 1 shows the battery performance of a carbon felt-supported tin composite negative electrode catalyst, its preparation method, and its application, as proposed in this invention.

[0040] Figure 19 Example 2 shows the battery performance of a carbon felt-supported tin composite negative electrode catalyst material, its preparation method, and its application, as proposed in this invention.

[0041] Figure 20 Example 3 shows the battery performance of a carbon felt-supported tin composite negative electrode catalyst material, its preparation method, and its application, as proposed in this invention.

[0042] Figure 21 Example 4 shows the battery performance of a carbon felt-supported tin composite negative electrode catalyst material, its preparation method, and its application, as proposed in this invention. Detailed Implementation

[0043] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0044] Example 1

[0045] A method for preparing a carbon felt-supported tin composite anode catalyst involves pretreating the carbon felt in air at a reaction temperature of 300℃ for 8 hours, followed by pretreatment. 7g of tin chloride pentahydrate is added to deionized water to prepare a 0.2mol / L tin chloride solution. After stirring, the pretreated carbon felt is added and stirred, then dried in a 60℃ oven. The solution is then heated at 800℃ in an argon atmosphere for 10 hours at a heating rate of 5℃ / min. Finally, the solution is washed three times with 0.1mol / L dilute hydrochloric acid and dried again in a 60℃ oven. The dried sample is then used as the anode in a vanadium redox flow battery for performance testing to evaluate the catalyst material's performance. The sulfuric acid system vanadium redox flow battery test conditions are as follows: both positive and negative electrodes are 36cm² carbon felt, and both use sulfuric acid vanadium redox flow battery electrolyte, which mainly contains 1MV³⁺, 1MVO²⁺, and 5MSO₄²⁻. The charge-discharge cycle was performed using a current density of 80mA / cm2. The charging cutoff condition was that the voltage was not higher than 1.6V, and the discharging cutoff condition was that the voltage was not lower than 0.8V.

[0046] Example 2

[0047] A method for preparing a carbon felt-supported tin composite anode catalyst involves pretreating the carbon felt in air at a reaction temperature of 350°C for 10 hours, followed by pretreatment. Then, 10.5 g of tin chloride pentahydrate is added to deionized water to prepare a 0.3 mol / L tin chloride solution. After thorough stirring, the pretreated carbon felt is added and stirred, then dried in a 60°C oven. The solution is then heated at 850°C in an argon atmosphere for 12 hours at a heating rate of 5°C / min. Finally, the solution is washed three times with 0.2 mol / L dilute hydrochloric acid and dried again in a 60°C oven. The dried sample is then used as the anode in a vanadium redox flow battery for performance testing to evaluate the catalyst material's performance. The sulfuric acid system vanadium redox flow battery test conditions are as follows: both the positive and negative electrodes are 36 cm² carbon felt, and the electrolyte used is sulfuric acid vanadium redox flow battery electrolyte, mainly containing 1 MV³⁺, 1 MVO²⁺, and 5 MSO₄²⁻. The charge-discharge cycle was performed using a current density of 80mA / cm2. The charging cutoff condition was that the voltage was not higher than 1.6V, and the discharging cutoff condition was that the voltage was not lower than 0.8V.

[0048] Example 3

[0049] A method for preparing a carbon felt-supported tin composite anode catalyst involves pretreating the carbon felt in air at a reaction temperature of 450℃ for 11 hours, followed by pretreatment. Then, 14g of tin chloride pentahydrate is added to deionized water to prepare a 0.4mol / L tin chloride solution. After stirring, the pretreated carbon felt is added and stirred, then dried in a 60℃ oven. The solution is then heated at 900℃ in an argon atmosphere for 13 hours at a heating rate of 5℃ / min. Finally, the solution is washed three times with 0.3mol / L dilute hydrochloric acid and dried again in a 60℃ oven. After drying, the sample is used as the anode in a vanadium redox flow battery for performance testing to evaluate the catalyst material's performance. The sulfuric acid system vanadium redox flow battery test conditions are as follows: both the positive and negative electrodes are 36cm² carbon felt, and the electrolyte used is sulfuric acid vanadium redox flow battery electrolyte, mainly containing 1MV³⁺, 1MVO²⁺, and 5MSO₄²⁻. The charge-discharge cycle was performed using a current density of 80mA / cm2. The charging cutoff condition was that the voltage was not higher than 1.6V, and the discharging cutoff condition was that the voltage was not lower than 0.8V.

[0050] Example 4

[0051] A method for preparing a carbon felt-supported tin composite anode catalyst involves pretreating the carbon felt in air at a reaction temperature of 500℃ for 12 hours, followed by pretreatment. Then, 21g of tin chloride pentahydrate is added to deionized water to prepare a 0.6mol / L tin chloride solution. After stirring, the pretreated carbon felt is added and stirred, then dried in a 60℃ oven. The solution is then heated at 1000℃ in an argon atmosphere for 15 hours at a heating rate of 5℃ / min. Finally, the solution is washed three times with 0.4mol / L dilute hydrochloric acid and dried again in a 60℃ oven. After drying, the sample is used as the anode in a vanadium redox flow battery for performance testing to evaluate the catalyst material's performance. The sulfuric acid system vanadium redox flow battery test conditions are as follows: both the positive and negative electrodes are 36cm² carbon felt, and the electrolyte used is sulfuric acid vanadium redox flow battery electrolyte, mainly containing 1MV³⁺, 1MVO²⁺, and 5MSO₄²⁻. The charge-discharge cycle was performed using a current density of 80mA / cm2. The charging cutoff condition was that the voltage was not higher than 1.6V, and the discharging cutoff condition was that the voltage was not lower than 0.8V.

[0052] Table 1 Performance Comparison Table:

[0053] Serial Number Catalytic materials Coulomb efficiency (%) Voltage efficiency (%) Energy efficiency (%) 1 blank 95.73 86.81 83.10 2 1 95.76 88.55 84.79 3 2 96.76 88.73 85.86 4 3 96.65 88.97 85.98 5 4 96.38 88.32 85.12

[0054] The data in the table show that, compared with the blank group, the carbon felt-loaded tin single-element cells all have excellent battery performance.

[0055] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a carbon felt-supported tin composite negative electrode catalyst, characterized in that, Includes the following steps: S1. High-temperature pretreatment of carbon felt: The carbon felt is placed in an air atmosphere for high-temperature pretreatment to obtain pretreated carbon felt. S2. Preparation of tin salt precursor solution: Dissolve tin salt in deionized water and stir until the tin salt is completely dissolved to obtain a uniform tin salt precursor solution. S3. Impregnation and drying: The pretreated carbon felt obtained in step S1 is immersed in tin salt precursor solution for full impregnation, and then dried after removal. S4. High-temperature in-situ reduction in argon atmosphere: The dried carbon felt is placed in an inert argon atmosphere for high-temperature heat treatment, which causes an in-situ reduction reaction, so that elemental tin is uniformly deposited and firmly loaded on the surface of the carbon felt and inside the carbon fibers, thus obtaining a preliminary composite material. S5. Washing and Drying: The preliminary composite material is washed multiple times with dilute hydrochloric acid to remove various impurities from the system. After drying, the carbon felt-supported tin anode catalyst material is obtained.

2. The preparation method of a carbon felt-supported tin composite negative electrode catalyst according to claim 1, characterized in that, In step S1, the high-temperature pretreatment temperature of the carbon felt is 300-500℃; the high-temperature pretreatment time of the carbon felt is 8h-12h.

3. The preparation method of a carbon felt-supported tin composite negative electrode catalyst according to claim 2, characterized in that, In step S2, the tin salt is tin chloride pentahydrate; the concentration of tin ions in the tin salt precursor solution is 0.2 mol / L-0.6 mol / L.

4. The preparation method of a carbon felt-supported tin composite negative electrode catalyst according to claim 3, characterized in that, In step S4, the high-temperature heat treatment temperature is between 800-1000℃; the high-temperature heat treatment time is between 10h-15h.

5. The preparation method of a carbon felt-supported tin composite negative electrode catalyst according to claim 4, characterized in that, In step S5, the concentration of the dilute hydrochloric acid used for washing is 0.1 mol / L-0.4 mol / L.

6. A carbon felt-supported tin composite anode catalyst, characterized in that, It is prepared by the preparation method according to any one of claims 1-5.

7. An application of a carbon felt-supported tin composite negative electrode catalyst, characterized in that, The carbon felt-supported tin composite anode catalyst of claim 6 is applied to the anode of an all-vanadium redox flow battery.